A single‐nucleotide polymorphism of miR‐146a and psoriasis: an association and functional study. Issue 11 (11th September 2014) - Zhang, Weigang; Yi, Xiuli; Guo, Sen; Shi, Qiong; Wei, Chao; Li, Xia; Gao, Lin; Wang, Gang; Gao, Tianwen; Wang, Lei; Li, Chunying
Abstract Epidermal growth factor receptor (EGFR), which is overexpressed in psoriatic lesions, has been proven to contribute to the hyperproliferation of keratinocytes in psoriasis. Single nucleotide polymorphisms (SNPs) involved in miRNAs that can regulate the expression of EGFR could potentially influence the development of psoriasis. The present study investigated the association between a functional SNP of rs2910164 in miR‐146a and the risk of psoriasis in the Chinese Han population. A total of 521 Han Chinese patients with psoriasis and 582 healthy controls were recruited in this study. The miR‐146a rs2910164 SNP was genotyped by polymerase chain reaction‐restriction fragment length polymorphism. Overall, a significantly increased risk of psoriasis was associated with the rs2910164 miR‐146a CG and GG genotypes (adjusted OR, 1.38; 95% CI, 1.06–1.80). Furthermore, the rs2910164G allele in miR‐146a attenuated its inhibitory regulation on the expression of EGFR as well as the proliferation of human keratinocytes, and lowered the level of miR‐146a in the psoriatic lesions. These findings indicate that the rs2910164G allele in miR‐146a weakens its suppression on the proliferation of keratinocytes probably through the decreased inhibition of the target gene, EGFR, which may account for the increased risk of psoriasis in this study population.